PEMETAAN POTENSI DAN STRATEGI PENGEMBANGAN UMKM DI KOTA GORONTALO - Ardi Hardian Pantu; Sri Indriyani S. Dai; Santoso, Ivan Rahmat (Universitas Mataram, 2023)
This study aims to analyze the mapping of potential and development strateg micro, small, and medium enterprises in gorontalo city. The data used in study are secondary data sourced from statistics Indonesia and the Departement of Industry and Trade of Gorontalo Province. This research uses Location Question, Shitf Share, and SWOT Analysis. The study results showed that (1) based on Mapping using the Location Question, the highest number of micro, small, and medium enterprises wa at the sub-district scale, namely Kota Barat sub-district, Gorontalo City. (2) Based on the Shift Share analysis, it was found that the highest Micro, Small, and Medium Enterprises industry was in the Processing Industry in Gorontalo City, (3) and based on the results of the SWOT analysis, the Government should encourage the growth of the Micro, Small and Medium Enterprises Industry in Gorontalo City.